Distorted Identity in Ahmed Saadawi’s Frankenstein in Baghdad - Salih, Huda Mohammed; Mohammed, Lawend Ikram (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This study examines the issue of distorted identities in Ahmed Saadawi's Frankenstein in Baghdad, set in post-2003 war-torn Iraq. The novel, inspired by Mary Shelley's Frankenstein, depicts a creature “Whatsitsname” created from the body parts of war victims, representing the fragmentation of both individual and national identity at a period of tremendous violence and instability. This study looks at how Saadawi depicts the collapse of personal and moral identities in the characters of Hadi, Mahmoud, and Baghdad residents as they deal with the horrors of war and occupation. Furthermore, the novel criticizes the erosion of Iraqi national identity, highlighting the profound sectarian splits that match the creature's fractured form. By examining the blurring lines between justice and vengeance, victim and offender, the study contends that Frankenstein in Baghdad is a profound meditation on the complicated process of identity building and destruction in combat zones. Additionally, the study adds to the increasing body of scholarship on Middle Eastern postwar fiction by highlighting how literary works can shed light on the sociopolitical reality of oppressed states.